Comparative Analysis of Initial Antibiotic Dosing Among Healthy Weight, Overweight, and Obese Children with Osteomyelitis. (4th October 2017) - Waddell, Joel; Mcculloh, Russell; Goldman, Jennifer; Lee, Brian; Teachout, Warren
Abstract: Background: Acute hematogenous osteomyelitis (AHO) is a common infection of childhood. Inadequately treated AHO can lead to significant morbidity. Small studies have demonstrated alterations in the pharmacokinetics of antibiotics among obese children. Consequently, there is no consensus regarding appropriate dosing of antibiotics among overweight and obese children with AHO. Methods: This is a single center, retrospective, cohort study of children 2–17 years of age with a discharge diagnosis of acute osteomyelitis admitted between 1/1/2012 and 12/31/2015. Complicated osteomyelitis cases were excluded. Variability of the initial mg/kg antibiotic dose was determined and compared between healthy weight, overweight, and obese children. Results: 142 children were included in the cohort. In total, 83 (58%) were classified as healthy weight, 25 (18%) overweight, and 34 (24%) obese. No difference was found in the variability of mg/kg dosing of vancomycin or clindamycin across the three weight groups. Cefazolin dosing in healthy weight children (median 33.3mg/kg [IQR 32.9–36.7mg/kg]) was significantly higher as compared with obese children (24.4mg/kg [20.0–33.3mg/kg]) ( P = 0.041). Cephalexin dosing in healthy weight children (33.0mg/kg [30.6–34.5mg/kg]) was also significantly higher than in obese children (23.0mg/kg [20.0–29.9mg/kg])( P = 0.013). Conclusion: There was significant variability and lower overall dosing of first-generation cephalosporins among obese children compared with healthy weight children. Given the increasing incidence of invasive methicillin-susceptible Staphylococcus aureus infections, this study highlights the need for practitioners to optimize first-generation cephalosporin dosing in obese children suffering from AHO. These data also call for future studies to determine the clinical outcomes in obese children with AHO in relation to dosing adequacy. Disclosures: All authors: No reported disclosures.